Climate Change and Global Warming - Amini, Ata (IntechOpen, 2019)
Strong evidence has proved that the climate is changing and the world is becoming warmer by various measures. It is now generally accepted that human activities are changing the configuration of our ecosystem. Most likely, further changes and negative influences are unavoidable. Nevertheless, we can prevent the dominant impacts of climate change, so that life remains manageable. Meanwhile, misperceptions of the solutions are increasing. The overall purpose of this book is to introduce the concept of climate change and its effects within the context of sustainable development. This book, Climate Change and Global Warming, brings together the engineers, scientists, socialists and policymakers of the world to critically look at various aspects of climate change, and it is an attempt to look at the facts.